2012
DOI: 10.1021/es300044h
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functionally Relevant Populations in Enhanced Biological Phosphorus Removal Processes Based On Intracellular Polymers Profiles and Insights into the Metabolic Diversity and Heterogeneity

Abstract: This study proposed and demonstrated the application of a new Raman microscopy-based method for metabolic state-based identification and quantification of functionally relevant populations, namely polyphosphate accumulating organisms (PAOs) and glycogen accumulating organisms (GAOs), in enhanced biological phosphorus removal (EBPR) system via simultaneous detection of multiple intracellular polymers including polyphosphate (polyP), glycogen, and polyhydroxybutyrate (PHB). The unique Raman spectrum of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 40 publications
3
69
0
Order By: Relevance
“…PolyP breakdown allows cells to survive during P limitation (12, 13), although some microbes transiently accumulate polyP upon nitrogen and P stress (8,14,15). Massive accumulation of polyP by certain bacteria sequesters dissolved P during biological wastewater treatment (16)(17)(18).While polyP is studied in a range of microbiological and environmental fields, the lack of easy quantitative methods has hampered progress. For example, polyP has very rarely been measured in the oceans despite increasing interest in the physiological responses of marine microbes to the ultralow P concentrations frequently found at sea and their biogeochemical implications (14,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PolyP breakdown allows cells to survive during P limitation (12, 13), although some microbes transiently accumulate polyP upon nitrogen and P stress (8,14,15). Massive accumulation of polyP by certain bacteria sequesters dissolved P during biological wastewater treatment (16)(17)(18).While polyP is studied in a range of microbiological and environmental fields, the lack of easy quantitative methods has hampered progress. For example, polyP has very rarely been measured in the oceans despite increasing interest in the physiological responses of marine microbes to the ultralow P concentrations frequently found at sea and their biogeochemical implications (14,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…PolyP breakdown allows cells to survive during P limitation (12, 13), although some microbes transiently accumulate polyP upon nitrogen and P stress (8,14,15). Massive accumulation of polyP by certain bacteria sequesters dissolved P during biological wastewater treatment (16)(17)(18).…”
mentioning
confidence: 99%
“…and it has since been shown that PAO are capable of utilizing both the TCA cycle and Glycolysis (Zhou et al, 2009). Some have suggested that some PAO may switch between metabolic pathways according to internal or external conditions (Acevedo et al, 2012(Acevedo et al, , 2014Majed et al, 2012;Lanham et al, 2013). Utilisation of glycolysis has been shown to yield more efficient P-removal rates than the TCA cycle, within the context of an enhanced CAS system (Lanham et al, 2013).…”
Section: Metabolism Of Paomentioning
confidence: 99%
“…Taking individual cells as the modeling units is justified considering that internal states and phenotypic traits of individual bacterial cells can be highly heterogeneous in populations, even in isogenic ones [22]. For example, a recent experimental study [23] showed that the internal state (i.e., the level of internally stored nutrients) of cells can vary significantly in a population.…”
Section: Modeling Units and Model Classificationmentioning
confidence: 99%